Supervisi dan Ketersediaan Buku KIA Terhadap Penggunaan Buku KIA oleh Bidan Desa - Muhdar Muhdar; Cahya Tri Purnami; Titi Suherni (Jurnal Manajemen Kesehatan Indonesia, 2019)
The high MMR of the government issued a Decree of the Minister of Health of the Republic of Indonesia concerning the MCH Handbook, stating that the MCH Handbook is a tool for early detection of disorders or health problems for mothers and children, so that when the MCH handbook is not utilized properly it will be difficult to detect early on mothers and child. The purpose of this study was to determine factors: perception of supervision and availability of MCH books influenced the use of MCH books. This type of observational quantitative research is cross sectional. The population of all village midwives is 124 people who work in 16 puskesmas working areas in Kolaka Regency. Sampling was done by simple rondom sampling method, obtained as many as 55 people who met the inclusion and exclusion criteria. The analysis uses moment or sperman’s rho product analysis, and multivariate analysis with linear regression test. Results: perception perception variables with Pearson's R. correlation test obtained r = 0.244 and p = 0.73 where the value of p> 0.05 means that there is no significant relationship between perception of supervision with the use of the MCH handbook. Variable availability of MCH books with the Spearman correlation test, s Rho obtained r = 0.157 and p = 0.25 where p> 0.05, which means there is no significant relationship between the availability of MCH books with the use of MCH books. Conclusion: the study found that the perception of supervision and provision of MCH books did not significantly influence the use of MCH books in antenatal services by village midwives in Kolaka District. Suggestions Kolaka District Health Office needs to increase the role of periodic supervision and procurement of MCH books in accordance with the target number and availability of MCH books at health service sites.